Incidence and risk factors of hypertension in children in the emergency department of Ibnu Sina Hospital Makassar - Sakti, Putri Amalia; Rauf, Syarifuddin; Jusli, Jusli; Darussalam, Andi Husni Esa; Badaruddin, Kartini (Institute of Computer Science (IOCS), 2024)
Background: Hypertension is rare in childhood, but it has become a significant concern for the community. This condition can lead to serious complications, including an increased risk of end-organ damage and the potential for early essential hypertension. This study aims to determine the incidence and risk factors for hypertension in children in the emergency department of Ibnu Sina Hospital Makassar. Methods: This research is descriptive observational design with a cross-sectional approach, collecting primary data through interviews and measurements of respondents. Results: A total of 191 pediatric patients visited the emergency room of Ibnu Sina Hospital. The age distribution was as follows: 13.6% were under 5 years old, 45.5% were between 5 and 11 years old, and 40.8% were 12 to 18 years old. The gender distribution was 46.1% male and 53.9% female. In terms of hypertension, 87.9% of the patients had normal blood pressure, 1.6% had elevated blood pressure, 6.8% were classified with grade 1 hypertension, and 3.7% had grade 2 hypertension. The nutritional status was as follows: 20.4% were obese, 15.2% were overweight, 32.9% were well-nourished, 19.9% were undernourished, and 11.6% were malnourished. In terms of family history of hypertension, 46.6% had a family history, while 53.4% did not. Additionally, 16.8% had a history of low birth weight (LBW), and 83.2% did not. Conclusion: Nutritional status varied significantly, with notable rates of obesity and undernourishment. Nearly half of the patients had a family history of hypertension, and a small percentage had a history of low birth weight.